Development and Evaluation of a Bilingual Banyumas Folklore-Based Interactive Audiobook for Early Childhood Language Skills - Ali, Musyafa; Prawening, Cesilia; Aji Jauhari Ma’mun, Ahmad; Aulia Nanda, Yuha; Wan Mokhtar, Wan Khairul Aiman (Al-Athfal: Jurnal Pendidikan Anak, 2026)
Purpose – Bilingual, folklore-based digital learning media for early childhood remain scarce, and no prior study has empirically tested a bilingual (Javanese-Indonesian) interactive audiobook grounded in local folklore for its effect on early childhood language skills. This study addresses that gap by developing a bilingual, Banyumas folklore-based interactive audiobook and evaluating its effect on children's vocabulary, listening, and speaking skills.Design/methods/approach – This study followed a Research and Development (R&D) design adapted from the Borg and Gall model (Borg & Gall, 1983) and modified by Sugiyono, comprising needs analysis, product design, expert validation, revision, and effectiveness testing. Participants were 58 kindergarten children (two classes of 29) at a state kindergarten in East Purwokerto, assigned to experimental and control groups. A pretest–posttest non-randomized control-group design was used, and product effectiveness was analyzed statistically (normality, homogeneity, independent t-test, and N-Gain).Findings – The independent-samples t-test confirmed the experimental and control groups were statistically equivalent at pretest (Sig. 2-tailed = 0.372 > 0.05), ruling out a pre-existing advantage. After treatment, the experimental group achieved a mean N-Gain of 67.57% (medium-high, "quite effective" category) versus 44.85% for the control group, a difference tested and found statistically significant (p < 0.05). Together, these results indicate that the improvement in language skills observed in the experimental group is attributable to the bilingual interactive audiobook intervention rather than to chance or baseline differences.Research implications/limitations – Limitations from this study in the number of samples, the scope of the development stage, and the relatively short duration of the effectiveness test.Practical implications – Teachers and parents can adopt the validated audiobook as a ready-to-use bilingual literacy tool that simultaneously builds language skills and introduces children to local (Banyumas) cultural heritage, offering an accessible alternative to conventional storytelling methods in kindergarten classrooms.   Originality/value – Unlike prior audiobook studies that are either monolingual or not grounded in local folklore, this study is among the first to empirically test a bilingual (Javanese-Indonesian), Banyumas-folklore-based interactive audiobook on early childhood language outcomes, using a controlled experimental design with 58 kindergarten children (29 experimental, 29 control) and statistically validated instruments (Cronbach's alpha = 0.65; Pearson item-total correlations). The resulting conceptual model integrates digital technology, local cultural wisdom, and bilingual pedagogy in a way not previously combined in the early-childhood-language literature.Paper type Research paper